Terapi Murottal Al-Quran Dalam Mengatasi Kecemasan Pada Anak Didik Di Lembaga Pembinaan Khusus Anak (LPKA) Banda Aceh - Izzatul Muzayyanah; Mahdi NK; Ismiati (Jurnal Seumubeuet, 2026)
Anxiety is a common psychological problem experienced by juveniles at the Special Development Institution (LPKA) resulting from restricted freedom, the demands of adapting to the institutional environment, and uncertainty about their future. One effort that can be implemented to reduce anxiety is through Qur’anic murottal therapy. This study aimed to describe the implementation of Qur'anic murottal therapy using Surah Ar-Rahman and to examine changes in the anxiety levels of juveniles at LPKA Banda Aceh. This study employed an experimental approach using a pre-experimental one-group pretest-posttest design was employed involving 10 participants selected through purposive sampling. Data were collected through observation, interviews, and anxiety assessments conducted before (pretest) and after (posttest) four sessions of Qur'anic murottal therapy. The findings indicated that Qur'anic murottal therapy was associated with a reduction in anxiety levels and produced positive changes in the participants' psychological well-being. Based on observations and interviews, the participants reported feeling calmer, more comfortable, better able to manage negative thoughts, more focused, and more optimistic. The anxiety assessment also demonstrated a decline following the intervention. Before the therapy, 70% of the participants were classified as having high to very high anxiety levels. After completing the therapy, anxiety levels decreased to the moderate category, with 50% of the participants falling into the low-anxiety category. These findings indicate that Murottal Al-Qur’an therapy using Surah Ar-Rahman has the potential to help reduce anxiety levels and support the psychological well-being of juvenile inmates during the rehabilitation process.